Prediction of golden time using SVR for recovering SIS under severe accidents. (August 2016) - Yoo, Kwae Hwan; Back, Ju Hyun; Na, Man Gyun; Kim, Jae Hwan; Hur, Seop; Kim, Chang Hwoi
Highlights: If the safety injection system is not working in time, the reactor vessel may be damaged. It is important to properly actuate the SIS before a DBA becomes a severe accident. Golden time is defined as the available time from an initial SIS malfunction for recovering SIS. A support vector regression (SVR) model was applied to predict the golden time. It was shown that the proposed SVR model could predict the golden time accurately. Abstract: Nuclear power plants (NPPs) are designed in consideration of design basis accidents (DBAs). However, if the safety injection system (SIS) is not working properly in a loss-of-coolant-accident (LOCA) situation, it can induce a severe accident that exceeds DBAs. Therefore, it is important to properly actuate the SIS before a DBA becomes a severe accident. If the SIS is not working in time, the reactor core may be uncovered and the reactor vessel (RV) may be damaged. In this paper, we defined the golden time as the available time from an initial SIS malfunction for actuating the SIS to prevent reactor core uncovery and RV failure. A support vector regression (SVR) model was applied to predict the golden time. The input variables and parameters of the SVR model were selected and optimized by using a genetic algorithm. The data set of severe accident scenarios was obtained by using the Modular Accident Analysis Program (MAAP) code. An optimized power reactor (OPR1000) was used for the simulations. It was shown that that the proposed SVR model could predict the golden time accurately.